Experiences of social work supervisors on supervising inexperienced social workers in the Department of Social Development Malamulele Area Office - Baloyi, Thembhani (University of Limpopo, 2017)
Social Work supervisors experience a lot of challenges when supervising inexperienced social workers. The overall aim of the study was to explore and describe experiences of social work supervisors in supervising inexperienced social workers in the Department of Social Development Malamulele Area Office. The study objectives were to identify supervisors’ training needs that enable them to manage inexperienced social workers; to appraise how supervisors manage poor confidence among inexperienced social workers; to assess how supervisors manage time to meet deadlines coupled with supervising; and to establish knowledge gaps between supervisors and inexperienced social workers in terms of relevant theories, skills and techniques. The researcher used both explorative and descriptive research designs. The data was collected through semi-structured face-to-face interviews from eight (8) social work supervisors who are employed by the Department of Social Development, Malamulele area office. The sample consisted of social work supervisors who were available and ready to participate in the study. Eight social work supervisors who had supervised inexperienced social workers were interviewed. The researcher followed the steps of thematic data analysis which are transcription of data, checking and editing, analysing and interpretation, and generalisation to analyse data. Ethical considerations such as voluntary participation, permission to conduct the study, anonymity, confidentiality and no harm to respondents were considered. The researcher found that Social Work supervisors who render supervision do not have relevant and up-to-date theoretical knowledge. They still apply relevant theories that they learned during their time as undergraduate Social Workers, and the fact that they do attend supervisory training makes the supervision to be poor. The researcher found that a lot of Social Work supervisors rely on their experiences because they do not have formal supervision training. The researcher also found that inexperienced Social Workers are not receiving enough supervision from their supervisors. The researcher concluded that these Social Workers are receiving enough supervision because their supervisors have a lot of work such as attending clients and meetings. Social Work supervisors in Malamulele area office are currently practising without supervisory training, but they are appointed based on their working experience. The researcher recommended that the Department of Social Development, Vhembe x District Municipality should encourage inexperienced Social Workers and supervisors to attend courses in supervision offered by different service providers and to understand their role.
Thesis (M. A. (Social Work)) -- University of Limpopo, 2017
Keywords: Social Work supervisor; Inexperienced Social Worker; Experiences; Supervision; Social workers -- Supervision of; Social workers -- South Africa -- Limpopo; Social service; Supervision of employees; Social work administration -- South Africa -- Limpopo